2015
DOI: 10.14218/jcth.2015.00010
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic Extrahepatic Manifestations of Hepatitis C

Abstract: Hepatitis C virus (HCV) affects millions of people worldwide, and an estimated 3.2 million people in the United States. HCV is a hepatotropic and lymphotropic virus that causes not only liver disease, but also a significant number of extrahepatic manifestations (EHMs). Up to 74% of patients affected by HCV will have HCV-related EHMs of some severity in their lifetime. The EHMs vary from simple cutaneous palpable purpura to complex lymphoproliferative disorders, including lymphomas and immune-complex deposit di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
0
15
0
2
Order By: Relevance
“…It has been reported that 20% of the patients with HCV have MC, but most have cryoglobulins levels of less than 6%, which is not clinically significant and that only 3% of HCV patients have clinically significant MC with cryoglobulins levels of more than 6% [ 23 , 24 ]. The mean cryocrit levels in HCV patients were determined to be about 2% [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 20% of the patients with HCV have MC, but most have cryoglobulins levels of less than 6%, which is not clinically significant and that only 3% of HCV patients have clinically significant MC with cryoglobulins levels of more than 6% [ 23 , 24 ]. The mean cryocrit levels in HCV patients were determined to be about 2% [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic lichen planus is considered a premalignant condition, especially when involving the oral cavity, and has the propensity to progress to squamous cell carcinoma. Although data are limited on the effect of the new direct acting antivirals on the cutaneous manifestations of CHC, there is evidence from earlier studies that dermatological EMs including porphyria cutanea tarda often resolve with treatment with pegylated interferon (peg-IFN) and ribavirin [ 18 – 20 ]. Data on the treatment effect on lichen planus, however, are conflicting, with both worsening of manifestations and regression having been reported [ 20 ].…”
Section: Dermatological Manifestationsmentioning
confidence: 99%
“… Reduced depression [ 51 ]. Resolution of dermatological EMs including porphyria cutanea tarda [ 18 – 20 ] and lichen planus, although data on the latter are conflicting with both worsening and regression having been reported [ 20 ]. Reduced stroke risk [ 62 ].…”
Section: Treatment Effectmentioning
confidence: 99%
“…Hepatitis C virus (HCV) infection affects about 200 million people worldwide, being a major health problem [ 65 ]. HCV infection is associated with a high spectrum of extrahepatic disorders, including dermatological manifestations such as Sicca syndrome and lichen planus [ 66 ]. Some reports suggest a link between HCV and psoriasis as well [ 67 ].…”
Section: Psoriasis and Hepatitis C Virus Infectionmentioning
confidence: 99%